Metabolic muscle damage and oxidative stress markers in an America`s Cup yachting crew - Barrios, C.; Hadala, M.; Almansa, I.; Bosch-Morell, F.; Palanca, J. M.; Romero, F. J. (European Journal of Applied Physiology, 2011)
Activities of enzymes involved in muscle damage [creatine kinase (CK) and aspartate aminotransferase (AST)] and levels of malondialdehyde (MDA) as a marker of oxidative stress were monitored in the plasma of 27 members of an America`s Cup yachting crew. The preventive benefits of allopurinol on muscle damage were also tested. In racing period A, the crew was divided into two groups according to their tasks on board. Blood samples from all 27 sailors were obtained before the start of a 5-day fleet race, after the last race, and after the ten match races. In period B, crew members were divided at random into two groups. One group (13 participants) received 300 mg/day of allopurinol 3 h before racing. The other ten members received placebo. Blood samples were collected just before and after the second round of the Louis Vuitton Cup. All participants showed increased CK and AST activities after the racing period A. The increase in CK activity was highest in sailors involved in strenuous physical work. At the end of period A, plasma MDA levels were higher in all participants as compared with non-participant athletes. In period B, a significant decrease in CK activity, but not in AST, appeared among participants receiving allopurinol. Plasma MDA decreased in sailors treated with allopurinol, but this reduction did not reach statistical significance. America`s Cup is a sailing sport with high physical demands, as shown by the increase in muscle-damage markers. Treatment with allopurinol appeared to decrease the levels of muscle damage markers.